Characterization of Sludge Resulting from Chemical Coagulation and Electrocoagulation of Pumping Water from Fishmeal Factories - Aguilar Ascón, Edwar (2023)
In the fishmeal industry, seawater is used to transport fish to the factories. Due to this, “pumping water” with high concentrations of organic matter is generated that is treated via chemical coagulation before letting it into the sea. The objective of this study is to characterize and compare the sludge obtained from conventional chemical coagulation and the sludge from the electrocoagulation process. A pilot electrocoagulation plant was built next to a chemical coagulation plant. The sludge obtained from both methodologies was analyzed for its proximal composition, its iron and aluminum content, and the fatty acid profile in its contained fat. Electrocoagulation was found to produce sludge with a higher concentration of lipids and ash, which indirectly confirmed that it removes more organic pollutants and salts than chemical coagulation. The contents of aluminum and iron in the sludge obtained by electrocoagulation were 4.2% and 0.025%, respectively, while those in the sludge obtained from chemical coagulation were 0.01% and 4.8%, respectively. Aluminum comes from the sacrificial electrode of the electrocoagulation tank, while iron comes from the salts used in chemical coagulation. The sum of w-3 fatty acid values (EPA + DHA) was 12.5% and 18.8% for sludges from the electrocoagulation and chemical coagulation processes, respectively, so we can assume that electrocoagulation is a more oxidizing process than chemical coagulation. Due to their high organic load, both sludges must be assessed as an alternative feed ingredient.